Potential of Rice Husk-based Activated Carbon (RHAC) for Blowdown Cooling Water System in Oxygen-Free Copper (OFC) Rod Casting: A Review - Yasmin Annisa (University of Jember, 2025)
OFC rod is an ultra-pure copper conductor with low oxygen content (<10 ppm). The casting industry commonly uses continuous upward casting with an induction furnace, where cooling water plays a crucial role in stabilizing furnace temperature and supporting the solidification process. However, indirect metal contamination may occur, requiring blowdown to maintain product quality. The resulting contaminated blowdown water can harm the environment if discharged untreated. Activated carbon is a suitable adsorbent for removing heavy metals, particularly mesoporous activated carbon, such as Rice Husk-based Activated Carbon (RHAC). Rice husk biomass is rich in silica and carbon, making it an effective precursor to produce activated carbon. This review highlights the novel application of RHAC for treating blowdown water from the Oxygen-Free Copper casting process, an area that has received limited attention in previous research. A systematic review of peer-reviewed studies focused on activation methods, structural properties, adsorption mechanisms, and operating parameters of RHAC. RHAC possesses high porosity, a large surface area, and oxygen-containing functional groups (–OH, –ROH, –COOH, and C=O) that enable the effective adsorption of metal ions (Pb²⁺, Cd²⁺, and Fe²⁺) through ion exchange, complex formation, electrostatic interactions, and localized precipitation. Under optimized conditions, RHAC achieves removal efficiencies up to 98.49%. Its adsorption performance depends on pH, contact time, dosage, initial concentration, temperature, and pore structure. Integrating RHAC in a fixed-bed column with reverse osmosis and filtration offers a sustainable and cost-effective approach for wastewater management and water reuse in the copper casting industry.